PENGARUH LINGKUNGAN KERJA TERHADAP KUALITAS PELAYANAN PADA DINAS PANTI SOSIAL LANJUT USIA KOTA BIMA PROVINSI NTB - Zidan, Muh. Zinedin; Wulandari, Wulandari; Yusuf, Muhammad (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Public sector organizations are required to provide excellent service by making customer satisfaction the main goal for service personnel in accordance with public service standards in Law no. 25 of 2009 concerning Public Services. In addition to improving service quality through excellent service, public organizations must also provide quality services with the concept of